Các loài nấm rễ cộng sinh dưới tán rừng thông tỉnh Lâm Đồng - Tôn, Thất Minh (Trường Đại học Đà Lạt, 2012)
In two years 2007 and 2008, by investigating the mycorrhiza, which has symbiotic relationships with the roots pine tree forest, in the fields of Daolat city, Lac Duong, Don Duong and Lam Ha districts, we have detected and described 6 orders, 13 families, 21 genera and 68 species including 32 edible and 36 inedible species.